KARAKTERISTIK PENDERITA GANGGUAN JIWA PENYALAHGUNAAN NAPA (NARKOTIKA, PSIKOTROPIKA, DAN ZAT ADIKTIF) DI PANTI SOSIAL PAMARDI PUTRA “INSYAF’ SUMATERA UTARA TAHUN 2014 - lamtiur junita bancin; Rasmaliah .; Taufik Ashar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTMental disorders are psychological or behavioral disorders that occur in people, generally related to affective disorders, behavior, thoughts, and perceptions One of type from mental disorder according to Classification of Mental Disorder Diagnosis by health department is a mental disorder drug abuse. Drug Abuse cases in the world reached 300 million in 2010 The aim of this research is to know the characteristic of mental disorder of drug abuse in Panti Sosial Pamardi Putra “Insyaf” SUMUT. Design of this research is case series design and population is 120 data (total sampling) Highest proportion of mental disorder of drug abuser at age group 15-25 (58,3%), male (100%), Batak (53%), high school (70,5%), Student and Collegian (36%), Unmarried Status (77%), Shabu (35%), multiple substance combination Shabu, Marijuana, and Alcohol (30,8%), Behavioral disorder (50%), thought and behavioral disorder (50%), reason of abusing drug with environment factor (70%), length of using ≤ years, pharmacotherapy and psychotherapy treatment (69,2%), length of treatment ≥ 9 bulan, finishing treatment (67%. It is significant between ages and length of using (p=0,000), treatment kind and substance using (p=0,03), work with length of using (p=0,000), length of treatment and condition when go home (p=0,000), drug kinds and early symptoms (p=0,000) It is necessary that role for educational institutions, family and society environment, in the growing of the children behavior. Therefore it is necessary to give early promotion and socialization related to the danger of illcit drugs. Besides that, roles of social worker and counselor are needed in rehabilitation for drug abuser especially the mental record in detail and condition after finishing treatment. It will help to be a good material to evaluate in improving rehabilitation services.